Die predikantsamp. Deel 4: Predikantwees in die Gereformeerde tradisie in die 21ste eeu – nuwe uitdagings en nuwe tendense - Burger, CW (Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
The office of the minister. Part 4: On being a minister in the Reformed tradition in the 21st century – new challenges and new tendencies. The argument from the previous three articles is taken a bit further in this fourth article. In this article the focus is specifically on newer developments regarding the office of the minister in the Reformed tradition. Firstly traditional views is highlighted, especially looking at developments in the 20th century. Thereafter five new accents are looked at that came to the fore in the last twenty years. These accents are not very different to the accents of Calvin concerning this office, but it helps us to understand these accents within a new context. What is however still needed is the integration of these insights within a coherent whole – and this will be the aim of the last article of this series.